Impressive and durable clinical responses obtained with dabrafenib and trametinib in low-grade serous ovarian cancer harbouring a BRAF V600E mutation - Bárbara Lima; Miguel Henriques Abreu; Susana Sousa; Carla Bartosch; Deolinda Pereira (Elsevier, 2022)
Low-grade serous ovarian cancer (LGSOC) is now considered a different entity from high-grade serous ovarian cancer. The chemoresistance inherent to this type of ovarian cancer narrows the therapeutic options, especially in the recurrent setting. It is thought that the mitogen-activated protein kinase (MAPK) pathway plays a significant role in the pathogenesis of these tumours, and about 2 to 20% of LGSOC harbour a BRAF mutation. Here we present a case report of two patients with a BRAF V600E mutation that achieved sustained clinical responses with combination treatment with dabrafenib (BRAF inhibitor) and trametinib (MEK inhibitor).